EVALUATING THE FACTORS INFLUENCING ONLINE SHOPPING AND ITS CONSUMER SATISFACTION IN PUNE AREA - Rupali, Rajesh (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of study is to develop an understanding the factors which are influencing for online shopping in Pune area and to explore the demographic factors which influences the level of customer satisfaction of online shoppers. Exploratory research method is used. Survey method is used for data collection through structured questionnaire based on demographic profile like gender, age, duration and frequency of online shopping etc. 114 samples were scored on the basis of thirty-four variables of influencers and satisfaction of online shoppers in Pune area from Maharashtra State in India. The statistical tools for non-parametric data like Mann Whitney Test, Kruskal Wallis Test are used for data analysis. The finding of the study reveals that online customers age does not have influencing role in preferring factors for online shopping whereas male and female, prefers same parameters for online shopping as well as for customer satisfaction and after sales services. Study covers FMCG product Apparels like T-shirt, jeans, formals, casuals, ethnic and Accessories category like watches, sunglasses, handbags, jewellery and Shoes and sandals. Research will help the e-retailers for promoting their brands in online market targeting to digital customers and can boost the sale by framing appropriate marketing strategies aiming to demographics, shopping experience and satisfaction.